2022
DOI: 10.1001/jamaneurol.2022.0429
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical Neuronal Correlates of Sleep in Neurodegenerative Diseases

Abstract: IMPORTANCESleep disturbance is common among patients with neurodegenerative diseases. Examining the subcortical neuronal correlates of sleep disturbances is important to understanding the early-stage sleep neurodegenerative phenomena.OBJECTIVES To examine the correlation between the number of important subcortical wake-promoting neurons and clinical sleep phenotypes in patients with Alzheimer disease (AD) or progressive supranuclear palsy (PSP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 59 publications
2
50
0
Order By: Relevance
“…The relationship between NfL and parameters of hypoxemia in OSA patients suggest a different mechanism, potentially via increased oxidative stress and neuroinflammation causing neurodegeneration ( Daulatzai, 2015 ; Snyder et al, 2017 ) and white matter disease ( Rostampour et al, 2020 ; Zacharias et al, 2021 ), which may contribute to sleepiness ( Xiong et al, 2017 ). Although tau-related neurodegeneration of wake-promoting neurons can start in pre-clinical stages of AD ( Braak et al, 2011 ; Stratmann et al, 2016 ), and could contribute to sleepiness ( Oh et al, 2022 ), it is unknown whether it could be associated with higher NfL levels. We have shown that CU late middle-aged and older adults with EDS have decreased cortical thickness ( Carvalho et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between NfL and parameters of hypoxemia in OSA patients suggest a different mechanism, potentially via increased oxidative stress and neuroinflammation causing neurodegeneration ( Daulatzai, 2015 ; Snyder et al, 2017 ) and white matter disease ( Rostampour et al, 2020 ; Zacharias et al, 2021 ), which may contribute to sleepiness ( Xiong et al, 2017 ). Although tau-related neurodegeneration of wake-promoting neurons can start in pre-clinical stages of AD ( Braak et al, 2011 ; Stratmann et al, 2016 ), and could contribute to sleepiness ( Oh et al, 2022 ), it is unknown whether it could be associated with higher NfL levels. We have shown that CU late middle-aged and older adults with EDS have decreased cortical thickness ( Carvalho et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This feed-forward loop hypothesis is corroborated by another study that showed that severity of OSA was associated with greater brain amyloid PET deposition only in amyloid positive participants ( Sharma et al, 2018 ). Additionally, participants with higher amyloid levels are more likely to have increased tau pathology affecting wake-promoting neurons ( Stratmann et al, 2016 ; Oh et al, 2019 , 2022 ), which could also contribute to sleepiness.…”
Section: Discussionmentioning
confidence: 99%
“…A more severe neuronal loss of several arousal‐promoting brain nuclei, including Hcrt neurons, LC NA neurons, tuberomamillary nucleus (TMN) histaminergic neurons, in post‐mortem brains of AD patients with tauopathy has been observed 16 . In a longitudinal clinical cohort study, more surviving Hcrt and TMN neurons correlated with decreased homeostatic sleep drive, shorter sleep bout duration, and greater percentage of wakefulness after sleep onset, 17 indicating an upregulation of excitability in these neurons. The glymphatic system promotes movement of cerebrospinal fluid into the brain and clears metabolic waste with a more efficient clearance during sleep 18 .…”
Section: Figurementioning
confidence: 99%
“…More tau- Tau Modulation by Circadian Rhythm positive neurons were found in sleep-regulating brainstem regions in parallel with the depletion of the total quantity of sleep and slow-wave activity during sleep [11]. The extension of tau pathology and neurodegeneration into the core circadian regions like the suprachiasmatic nucleus and its connecting regions, including the hypothalamus and brainstem, is regarded as a primary mechanism of circadian dysregulation in tauopathies [10,12]. In the viewpoint that circadian oscillation affects many brain functions and the impairment of the sleep-wake cycle increases the risk of neurodegenerative disease [13], the scenario in a reverse direction, circadian disruption gives an impact on tauopathies, is also possible.…”
Section: Introductionmentioning
confidence: 99%
“…From the very early stage of AD, instability in circadian rhythms reveals deficient slow-wave activity during the deep-sleep stage, and it seems to be strongly associated with tau pathology on tau-PET and tau levels in cerebrospinal fluid [ 9 ]. A recent postmortem study demonstrated an increased number of tau-positive and pTau-positive neurons in the subcortical wake-promoting area was significantly correlated with the disturbances in sleep variables in AD patients [ 10 ]. Similar results have been reported in the animal model, P301S tau transgenic mice presenting tau pathology.…”
Section: Introductionmentioning
confidence: 99%